Inferências textuais para compreender textos multimodais: uma proposta interventiva - Leandra Ines Seganfredo Santos, Rosimeri Mirta Fischer (Revista Leitura, 2019)
Este artigo discorre sobre alguns aspectos do projeto de intervenção “Inferências textuais como estratégias metacognitivas: uma proposta de compreensão de textos multimodais” proposto pelo Programa de Pós-Graduação Profissional em Letras – PROFLETRAS, UNEMAT, campus de Sinop/MT. Tem como objetivo compreender como ocorre o processo de ativação ou construção de inferências textuais por meio de estratégias cognitivas e metacognitivas para a compreensão de textos multimodais (propaganda). Para o desenvolvimento do projeto utilizou-se a pesquisa qualitativa (BORTONI-RICARDO, 2008) associada ao método de pesquisa-ação (THIOLLENT, 1996). A produção de dados deu-se com atividades escritas, pausa protocolada, técnica do cloze, relato interpretativo digital e protocolos de leitura verbalizados. A pesquisa ocorreu na Escola Municipal Professor Jari Edgar Zambiasi, no município de Aripuanã/MT, com alunos do 9º ano A. Constatou-se que o projeto melhorou e ampliou a compreensão leitora dos estudantes, pois conseguiram ativar e produzir inferências durante as atividades. Textual inferences to comprehend multimodal texts: an intervention proposal This paper approaches some aspects related to mediaton and the improvement of reading comprehension developed in the intervention project “Textual inferences as metacognitive strategies: a proposal of multimodals texts comprehension”¹, presented for the Programa de Pós-graduação Profissional em Letras – Profletras, Unemat, Sinop campus. It aims to understand how the activation, or the construction, of textual inferences take place by means of cognitive, or metacognitive, strategies for the multimodals texts comprehension. For the development of the project we used the qualitative research (BORTONI-RICARDO, 2008) associated with the action research method (THIOLLENT, 1996). The data was collected using writing activities, protocoled reading, cloze procedure, digital interpretative account and reading aloud of reading protocols. The research took place at Escola Municipal Professor Jari Edgar Zambiasi, in the city of Aripuanã/MT, with students of 9th grade. The project improved and extended the student’s reading comprehension, once they activated and produced inferences during the development of cognitive and metacognitive activities. These supported the reflection about the built informations and the solution to textual comprehension problems while those allow the activation of knowledge stored in memory. DOI: 10.28998/2317-9945.2020n64p20-32